2001
DOI: 10.1161/hq1201.100224
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 and Relations to Fatty Acid Composition in the Diet and in Serum Cholesterol Esters

Abstract: Abstract-High plasminogen activator inhibitor (PAI)-1 levels and poor dietary fat quality are potential risk factors for cardiovascular disease. The aim was to investigate the cross-sectional associations between PAI-1 activity and dietary nutrient intake, focusing on fat quality, in a population-based study of 871 men aged 70 years. The relationship between PAI-1 and the fatty acid composition in serum cholesterol esters (nϭ381 men) was also studied. The estimated total fat intake was positively associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
6
15
1
Order By: Relevance
“…FAs of the nҀ3 family are generally regarded as being protective against cardiovascular disease (28,29), which is supported by our results, ie, a higher nҀ3 PUFA factor (factor 3) score was negatively associated with MetS. D5D activity in skeletal muscle membranes was previously shown to be associated with better insulin sensitivity (30,31), and previous studies in the ULSAM cohort showed that low D5D activity independently predicts MI (15) and that D5D activity is negatively associated with plasminogen activator inhibitor 1 (32). The positive loading from ⌬9 -18 in factor 3 ( Table 2) might seem surprising, because high SCD-1 activity is associated with insulin resistance.…”
Section: Tablesupporting
confidence: 88%
“…FAs of the nҀ3 family are generally regarded as being protective against cardiovascular disease (28,29), which is supported by our results, ie, a higher nҀ3 PUFA factor (factor 3) score was negatively associated with MetS. D5D activity in skeletal muscle membranes was previously shown to be associated with better insulin sensitivity (30,31), and previous studies in the ULSAM cohort showed that low D5D activity independently predicts MI (15) and that D5D activity is negatively associated with plasminogen activator inhibitor 1 (32). The positive loading from ⌬9 -18 in factor 3 ( Table 2) might seem surprising, because high SCD-1 activity is associated with insulin resistance.…”
Section: Tablesupporting
confidence: 88%
“…Low estimated D5D activity significantly predicted the development of metabolic syndrome in the present study, independently of lifestyle factors (smoking, physical activity and BMI) assessed at baseline, as well as the estimated activity of SCD-1 and D6D. Previous studies have reported decreased estimated D5D activity as an independent risk factor for myocardial infarction [24], and Byberg and colleagues found estimated D5D activity to be negatively associated with PAI-1 activity [27]. Our data might indicate that low estimated D5D activity is an early sign of the risk of developing metabolic syndrome, which 20 years later results in manifest metabolic syndrome.…”
Section: Discussionsupporting
confidence: 57%
“…In this same group of transplanted patients we found that plasma PAI-1 activity was significantly elevated and correlated positively with CRP, fasting insulinemia, and the HOMA index [4]. The finding in the present study of an association between plasma PAI-1 activity and total fat intake was expected [33]. The negative correlation between plasma PAI-1 activity and intake of saturated fatty acids is difficult to explain but may also be related to the diet, which included a smaller proportion of saturated than unsaturated fatty acids.…”
Section: Discussionsupporting
confidence: 78%
“…The negative correlation between plasma PAI-1 activity and intake of saturated fatty acids is difficult to explain but may also be related to the diet, which included a smaller proportion of saturated than unsaturated fatty acids. However, and probably as a consequence of the sample size, we could not find the positive correlation reported between intake of unsaturated fatty acids and plasma PAI-1 activity [33]. This thrombogenic effect of unsaturated fatty acids, if it really exists, is apparently paradoxical since it is widely believed that a high intake of unsaturated fatty acids protects against atherogenesis.…”
Section: Discussioncontrasting
confidence: 66%